2013
DOI: 10.1016/j.ceca.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

TRPM7 triggers Ca2+ sparks and invadosome formation in neuroblastoma cells

Abstract: Cell migration depends on the dynamic formation and turnover of cell adhesions and is tightly controlled by actomyosin contractility and local Ca2+ signals. The divalent cation channel TRPM7 (Transient Receptor Potential cation channel, subfamily Melastatin, member 7) has recently received much attention as a regulator of cell adhesion, migration and (localized) Ca2+ signaling. Overexpression and knockdown of TRPM7 affects actomyosin contractility and the formation of cell adhesions such as invadosomes and foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 66 publications
1
49
0
Order By: Relevance
“…It can interact with cytoskeletal components [78], [79] to modulate actomyosin contractility that is required for cell migration [80]. Over-expressing TRPM7 in a neuroblastoma cell line facilitated cell adhesion and formation of podosomes [78] and invadosomes [77], and inhibiting TRPM7 reduced migration of activated T cells [81]. TRPM7 whole-cell currents were of similar amplitude in unstimulated microglia and after treatment with LPS or a phorbol ester [19], as well as IL4 or IL10 (present study); however, the channel is regulated by several mechanisms that might affect the current in intact cells.…”
Section: Discussionmentioning
confidence: 99%
“…It can interact with cytoskeletal components [78], [79] to modulate actomyosin contractility that is required for cell migration [80]. Over-expressing TRPM7 in a neuroblastoma cell line facilitated cell adhesion and formation of podosomes [78] and invadosomes [77], and inhibiting TRPM7 reduced migration of activated T cells [81]. TRPM7 whole-cell currents were of similar amplitude in unstimulated microglia and after treatment with LPS or a phorbol ester [19], as well as IL4 or IL10 (present study); however, the channel is regulated by several mechanisms that might affect the current in intact cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among TRP channels, the transient receptor potential melastatin related 7 (TRPM7) channel is a Ca 2+ /Mg 2+ channel fused with a functional kinase domain that belongs to the α-kinase family [13], [14]. We and others showed that TRPM7 is involved in migration and/or invasion of epidermal cancer cells including neuroblastoma [15], [16], glioblastoma [17], breast cancer [18], [19], nasopharynx cancer [20], [21], lung cancer [22], prostate cancer [23], and PDAC [24], [25]. Importantly, TRPM7 is required for breast cancer metastasis formation in mouse xenograft, and high channel expression is an independent marker of poor outcome in breast cancer patients [26].…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ recordings were performed as described previously (Langeslag, Clark, Moolenaar, van Leeuwen, & Jalink, ; Visser et al, ). In short, cells were grown in 24 wells plate and incubated with Oregon Green 488 BAPTA‐1‐AM (Molecular Probes, USA) followed by further incubation in 2 ml DMEM F/12.…”
Section: Methodsmentioning
confidence: 99%